Management by design : applying design principles to the work experience - Rasmus, Daniel W., 1961- (Wiley, 2011)
"An innovative rethinking of work environments that puts the worker at the center that leads to improved performance. Management by Design: Applying Design Principles to the Work Experience explores the premise that the best way to attract and retain people, and their knowledge, will come by adopting the principles of design usually focused on customers, and turning it inward to create positive workplace experiences. The book Provides simple, flexible new approach to the design of workplace experiences Provides guidance on how to use technology, policy and practice and space as tools for workplace design Explains why it is more important than ever to manage work experiences, especially with the projected mismatch between need and talent already being felt across a wide range of industries Other titles by Rasmus: Listening to the Future: Why It's Everybody's Business This breakthrough book explores how scenarios can help organization envision their future more robustly, and navigate change in a way that makes them more adaptive and resilient."--Vydavatelská anotace
Keywords: organizace práce; pracovní prostředí; work design; work environment; monografie; monographs